Diversity and systematics of Middle-Late Ordovician calcified cyanobacteria and associated microfossils from Ordos Basin, North China. (January 2021) - Liu, Lijing; Wu, Yasheng; Bao, Hongping; Jiang, Hongxia; Zheng, Lijing; Chen, Yanlong
Abstract: Calcified cyanobacteria are of considerable research value for reconstructing the ecology of Paleozoic and Mesozoic benthic communities on carbonate platforms due to their ability to produce oxygen and fix nitrogen and CO2 . The diversity and abundance of calcified cyanobacteria was initially suggested to have declined in the Middle and Late Ordovician, although more recent work suggests that complex and diverse assemblages persisted throughout the Ordovician. Here, calcified cyanobacteria and associated microfossil flora from the Middle and Late Ordovician of the Ordos Basin, North China Block, are systematically described for the first time based on 1330 thin sections from seven outcrop profiles and four drill cores. In total, there are 18 species belonging to 16 genera, including a new species, Proaulopora ordosia n. sp. Girvanella, Subtifloria, Acuasiphonoria, Xianella, and Oscillatoriaceae gen. indet. are assigned to Osillatoriales of cyanobacteria; Ortonella, Hedstroemia, Cayeuxia, Zonotrichites, Proaulopora, and Phacelophyton are assigned to Nostocales of cyanobacteria; and Garwoodia, Renalcis, Izhella, Rothpletzella, and Wetheredella are assigned to calcified Microproblematica. A literature survey of Ordovician microfloral assemblages shows that cyanobacteria and associated microfossils occur in reef, open platform, lagoon, and tidal facies. Most genera occur on at least two independent blocks, and many have a cosmopolitan distribution in similar sedimentary facies. Our research suggests that calcified cyanobacteria and associated microfossils formed complex ecosystems and played greater ecological roles on carbonate platforms during the late Middle and Late Ordovician than was previously thought. UUID: http://zoobank.org/1812ccf8-136c-4cff-92ba-faeaf06523ef